What do we mean when we talk about constituency service? A scoping literature review of four decades of research - Edalina Rodrigues Sanches; João Conduto; André Marinha; Ana Espírito-Santo (Political Research Exchange)
Constituency service is a crucial concept for understanding the nature and intensity of the links between representatives and their constituents. However, studies have been inconsistent about the meaning of constituency service, its causes and consequences, justifying a systematic analysis of where we stand in this field of studies. This article conducts a scoping literature review of 198 studies on constituency service published between 1975 and 2021. It aims to answer the following questions: how has constituency service been defined? Which research designs are commonly used when studying it? And what are its driving factors and political effects? These questions are answered using a dataset that codes each study along several dimensions tapping into conceptualization, research design, explanatory factors, and effects. The analysis shows that this field of research has grown significantly over the last decade, covering more activities (inside and outside the geographic constituency) and countries, with increased methodological pluralism. This review makes an original contribution by charting the main trends in the study of constituency service, advancing a dynamic conceptualization of constituency service, and opening up new avenues for research on the subject.